2020
DOI: 10.3389/fmed.2020.00248
|View full text |Cite
|
Sign up to set email alerts
|

The Lung, the Heart, the Novel Coronavirus, and the Renin-Angiotensin System; The Need for Clinical Trials

Abstract: Angiotensin-converting enzyme 2 (ACE2) is the receptor for COVID-19 (SARs-CoV-2). ACE2 protects the lung and heart from acute respiratory distress syndrome (ARDS) and acute myocarditis and arrhythmias, because it breaks down Angiotensin II, which has inflammatory effects in the lung and heart as well as in the kidney. When SARS-CoV-2 binds to ACE2, it suppresses it, so this protective action of ACE2 is lost. Death from COVID-19 is due to ARDS and also heart failure and acute cardiac injury. Drugs that prevent … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
34
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 39 publications
(34 citation statements)
references
References 52 publications
0
34
0
Order By: Relevance
“… *The threshold for clinically significant effect (harm) was arbitrarily established as an increase of 25% in the odds of the outcome (a measure suggested by GRADE [43] ). CI: Confidence interval; OR: Odds ratio.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“… *The threshold for clinically significant effect (harm) was arbitrarily established as an increase of 25% in the odds of the outcome (a measure suggested by GRADE [43] ). CI: Confidence interval; OR: Odds ratio.…”
Section: Resultsmentioning
confidence: 99%
“…The potential role of ACE2 in the case of SARS-CoV-2 infection is still ambiguous. While its increase may supply pathways for SARS-CoV-2 entrance into the cells [2] , it is known that cleaved and shedded ACE2 leads to the breakdown of Angiotensin II to Angiotensin 1-7 (directly or indirectly increased with ARB or ACEi, respectively) have anti-inflammatory and anti-fibrotic effect through Mas receptors [41] , [43] . The SARS-CoV-2 infection also leads to a downregulation of ACE2, that was associated with increased lung injury in animal models [44] , [45] .…”
Section: Discussionmentioning
confidence: 99%
“…This score, in essence, quantifies the stability of the docked complex by optimizing global minimum energy conformation of the complex [44, 45]. On the other side, while it is probable that a better stability of S-R complex could lead to an increased viral load and maybe an increased infectivity, previous works showed that the spike protein – hACE2 complex is crucial for viral pathogenesis by causing acute lung damage [46, 47], which suggests a direct link between S-R complex stability and fatality rate. However, the robustness of the potential of S-R complex stability index for the spike protein variants as a tracker of fatality rate or disease severity needs to be studied in greater depths with more structured region-specific patient data (that are primarily available to selected government/non-government agencies) in connection with larger population-level sequence datasets for the given locations.…”
Section: Discussionmentioning
confidence: 99%
“…80 However, binding of SARS-CoV-2 to ACE2 alters functionality of the enzyme, which is discussed later. 80 Viral entry requires priming of the S protein by cellular proteases, which cleave the S protein at the S1/S2 and S2 site, allowing fusion of viral and cellular membranes. 77 SARS-CoV-1 and SARS CoV-2 both utilize the cellular serine protease TMPRSS2 and cathepsins B/L for S protein priming.…”
Section: Introductionmentioning
confidence: 99%